From byproduct to bioactive: genetic profiling, GC-MS, and nutritional analysis of citrus peel extracts for nutraceutical development - Prakash, Om; Kushwaha, Divya; Perveen, Kahkashan; Arzoo, Shaista; Gangola, Saurabh; Juyal, Vijay Kumar; Khan, Shifa; Vivekananda, (Frontiers in Plant Science, 2025)
The phytochemical, nutritional, and therapeutic qualities of citrus species (Rutaceae) make them significant on a global scale. Despite having a wealth of bioactive compounds with significant commercial and nutraceutical potential, citrus by-products, including peels, seeds, and pulp, are routinely discarded in large amounts. In this study, we examine the nutritional composition, elemental diversity, metabolite profile, and genetic variability of citrus species collected from various regions of Uttarakhand, India. Citrus peels are a good source of calcium (up to 104.10mg/100 g), zinc (58.3 mg/100 g), manganese (22.1 mg/100 g) and so on, as well as proteins (12.00 ± 0.11a), reducing and non-reducing sugar (136.45 ± .001a and 26.53 ± S1.123a), and vitamin C (65.56 ± 0.23a), according to elemental and nutritional analyses. On GC analysis, more than 45 bioactive compounds were identified, including rutin, limonene, linoelaidic acid, and palmitic acid. Citrus jambhiri (Almora) has the highest (51) phytochemicals, whereas Citrus sinensis (Pithoragarh) exhibits the lowest (27) phytochemicals. On genetic analysis, the accessions’ great diversity was further highlighted by a genetic analysis using Simple Sequence Repeat (SSR) markers, which showed grouping patterns related to species and geographic origin. Integrating biochemical, metabolite, and genetic data reveals a strong genotype–environment interaction that influences the nutritional and nutraceutical properties of citrus species. The study provides information that can aid in the development of functional foods, pharmaceutical applications, and crop enhancement methods while highlighting the potential of citrus by-products as sustainable sources of valuable bioactive compounds.